SOSIALISASI PEMANFAATAN MULTIMODEL DALAM PEMBELAJARAN PADA GURU SD NEGERI NO. 122372 PEMATANGSIANTAR - Juni Agus Simaremare; Herna Febrianty Sianipar (Fakultas Teknik, Universitas Bangka Belitung, 2021)
Participants in this multimode socialization activity were the teachers of SD Negeri No. 122372 Pematangsiantar, totaling 10 people. This socialization activity was carried out on Monday-Tuesday, 23-24 October 2018 starting at 09.00 WIB. This socialization activity aims to: (1) provide knowledge to teachers of SD Negeri No. 122372 Pematangsiantar nature and stages of implementation of multimodel in learning; (2) increase the creativity of SD Negeri No. 122372 Pematangsiantar in the learning process in the classroom. The method of implementing Community Service Activities is carried out in the form of socialization and direct practice in the classroom. This multimodel socialization activity has been carried out well according to the schedule of activities, starting from the initial, core and final activities. In general, teachers have been able to apply multimodel in learning according to the first phase to the fifth phase. This can be proven from 10 respondents 24.04% voted strongly agree that the use of multi-models in learning is very important and useful, while 75.96% said they agreed that the use of multi-models in learning is very important and useful.